2014
DOI: 10.2500/ajra.2014.28.4043
|View full text |Cite
|
Sign up to set email alerts
|

In-Office, Multisinus Balloon Dilation: 1-Year Outcomes from a Prospective, Multicenter, Open Label Trial

Abstract: In-office, multisinus balloon dilation is safe, effective, and well tolerated. Patients reported significant reductions in both sinonasal symptoms and health care use after balloon dilation. Efficacy observed at 1 and 6 month follow-up was sustained through 1 year with a very low rate of revision surgery. This study was a part of the clinical trial NCT01612780 registered at www.clinicaltrials.gov.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(54 citation statements)
references
References 30 publications
3
49
0
2
Order By: Relevance
“…10 Multiple studies, including a large patient registry of more than 1000 patients demonstrated that the technology appears to be safe, with rare complications. 3,11,12 In our survey, 21% of respondents reported experiencing a complication, including failed attempts at cannulation, scarring and/or adhesions, orbital complications, and significant bleeding. Only three individuals indicated that they had experienced or repaired CSF leaks caused by BCT.…”
Section: Discussionmentioning
confidence: 95%
“…10 Multiple studies, including a large patient registry of more than 1000 patients demonstrated that the technology appears to be safe, with rare complications. 3,11,12 In our survey, 21% of respondents reported experiencing a complication, including failed attempts at cannulation, scarring and/or adhesions, orbital complications, and significant bleeding. Only three individuals indicated that they had experienced or repaired CSF leaks caused by BCT.…”
Section: Discussionmentioning
confidence: 95%
“…The first goal of the present report was to provide data on this larger final study cohort and 24‐month follow‐up data. In addition to REMODEL, Entellus Medical (Plymouth, MN) sponsored five multicenter, prospective, controlled, single‐arm, standalone balloon dilation studies that are used in a meta‐analysis . Three of the five studies have been previously published in peer‐reviewed journals.…”
Section: Introductionmentioning
confidence: 99%
“…Current balloon technologies are applicable to the maxillary, frontal, and sphenoid sinuses, although there is some evidence that anterior ethmoid disease may respond to dilation of the ethmoid infundibulum which occurs in the course of maxillary ostial dilation. 285,286,1132 There have been many studies looking at the safety and efficacy of this technology, but few RCTs. The earliest RCT compared balloon dilation of the frontal recess vs ESS and found no significant difference in outcome.…”
Section: Ixe Aecrs: Complicationsmentioning
confidence: 99%
“…In another study, 9 patients with RARS were treated as part of a larger cohort using an office-based multi-sinus balloon dilation tool/technique. 286 Unfortunately, outcomes data specific to this small RARS group were not provided.…”
Section: Vid2 Rars Management: Essmentioning
confidence: 99%